CGIAR GENDER Impact Platform - CGIAR GENDER Impact Platform (CGIAR GENDER Impact Platform, 2023)
GENDER puts equality at the forefront of global agricultural research for development, both within and beyond CGIAR, to kickstart a process of genuine change toward greater gender equality, improved opportunities for youth and social inclusion. We envision greater social and gender equality driving food systems to become more productive, sustainable, resilient and equitable.